INTERNATIONAL EDUCATION IN AN INTERACTIVE VIRTUAL LEARNING ENVIRONMENT: EXPERIMENTING WITH DIGITAL MEDIA APPLICATIONS FOR COMMUNITY-BASED DEVELOPMENT - Dassin, Joan; Belda, Francisco Rolfsen [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2017)
The article draws on empirical data to assess learning outcomes from an interactive course on digital media for community development. Taught jointly through the Sustainable International Development program (SID) at Brandeis University and the State University of Sao Paulo (UNESP) graduate program on Media and Technology, the Learning Across Borders (LAB) course enabled international working groups to create digital media-based solutions to development challenges in health, education, environmental conservation, income generation and civic engagement. The purpose of the research was to test whether positive learning outcomes generated by a problem-and project-based pedagogical approach could occur in an international virtual learning environment. Digital technology created the learning environment and was also the topic of study, a convergence that further strengthened the course results. Based on a conceptual framework showing how information and communication technologies can enhance participatory development models, as well as on an analysis of student projects and survey data, the article concludes that the course format and implementation provide an innovative model for graduate level professional education in media and development.
Keywords: International education; Digital media; Community-based development; Virtual learning environment